Potensi Jus Buah Pare (Momordica Charantia L.) dalam Menurunkan Kadar Trigliserida pada Tikus Galur Wistar yang Diinduksi Diet Tinggi Lemak - Rindi Ariska Silalahi; Ilham Hariaji (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Hypercholesterolemia is one of the main factors that contribute to the development of life-threatening cardiovascular diseases. Bitter melon (Momordica charantia L.) is known to contain antioxidant compounds that have the potential to reduce cholesterol and triglyceride levels, making it an alternative natural treatment for hyperlipidemia. This study aims to evaluate the effectiveness of bitter melon juice in reducing triglyceride levels in Wistar rats induced by high-fat feed. This study used a true experimental design with a pretest-posttest with control group design. A total of 24 Wistar rats were induced with high-fat feed and divided into four groups: negative control, positive control, treatment group 1 (given bitter melon juice 1.8 mL), and treatment group 2 (given bitter melon juice 2.7 mL). Data analysis was performed using paired t test... A significant decrease in triglyceride levels was found in the groups given bitter melon juice 1.8 mL (p < 0.003) and 2.7 mL (p < 0.001) compared to the control group. Higher doses showed greater effectiveness in reducing triglyceride levels... Bitter melon (Momordica charantia L.) juice was shown to be effective in reducing triglyceride levels in Wistar rats induced by high-fat diet. These findings support the potential of bitter melon as a natural intervention to manage hyperlipidemia..